Professional identity formation in contemporary higher education students - Tomlinson, Michael; Jackson, Denise (Studies in higher education (Dorchester-on-Thames), 2021)
The study examines the prevalence of emergent professional identity (PI) among different groups of higher education students as well as the determining factors in the formation of PI. Drawing on evidence from a survey among Australian and UK students (N = 433), from two institutions and across a range of disciplines, empirical and conceptual insights are developed on the formation and impacts of students' professional identity. The article shows the significance of identity formation as a crucial bridge between higher education and future employment and its mediation by other key resources - in particular social and cultural capital - that students acquire before entering the labour market. The relative strength of identity formations can impact on students' sense of familiarity, proximity, and confidence around targeted employment areas. The article finally discusses the implications this has for individuals and institutions.